2021
DOI: 10.1038/s41467-021-25618-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated exome and RNA sequencing of TFE3-translocation renal cell carcinoma

Abstract: TFE3-translocation renal cell carcinoma (TFE3-tRCC) is a rare and heterogeneous subtype of kidney cancer with no standard treatment for advanced disease. We describe comprehensive molecular characteristics of 63 untreated primary TFE3-tRCCs based on whole-exome and RNA sequencing. TFE3-tRCC is highly heterogeneous, both clinicopathologically and genotypically. ASPSCR1-TFE3 fusion and several somatic copy number alterations, including the loss of 22q, are associated with aggressive features and poor outcomes. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 55 publications
(62 reference statements)
2
117
0
Order By: Relevance
“…Furthermore, TFE3 could promote the endolysosomal deprivation reaction by inducing the expression of autolysosomal genes [ 33 , 34 ]. Recently, Zeng et al demonstrated that lysosomal and autophagy pathways were significantly upregulated in TFE3-tRCC [ 35 ]. Previous studies indicated that elevated doses of crizotinib can induce autophagy in alveolar rhabdomyosarcoma cells [ 36 ] and that autophagy is required for crizotinib-induced apoptosis in MET-amplified gastric cancer cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TFE3 could promote the endolysosomal deprivation reaction by inducing the expression of autolysosomal genes [ 33 , 34 ]. Recently, Zeng et al demonstrated that lysosomal and autophagy pathways were significantly upregulated in TFE3-tRCC [ 35 ]. Previous studies indicated that elevated doses of crizotinib can induce autophagy in alveolar rhabdomyosarcoma cells [ 36 ] and that autophagy is required for crizotinib-induced apoptosis in MET-amplified gastric cancer cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients most often present with advanced and aggressive metastatic disease, with a median overall survival after diagnosis of approximately 18 months [ 18 ]. Some fusion partners such as ASPL/ASPSCR1-TFE3 fusion have been associated with having worse outcomes [ 19 , 20 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
“…Taking advantage of recent advances in the prognostic significance of certain fusion partners, this powerful technique could become the future gold standard for diagnosis. Whole exome sequencing can also be used to identify fusion partners with the advantage of providing other interesting information regarding copy number variation or variation in other genes that may impact patient outcomes or predict treatment efficacy [ 20 , 30 ].…”
Section: Molecular Featuresmentioning
confidence: 99%
See 2 more Smart Citations